Comparative analysis and ways of integration of Schema Therapy and Narrative Psychotherapy - Abramov, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article compares schema-therapy to narrative therapy across three domains: (i) theoretical methodological and philosophical framework; (ii) technics (both methods and their theoretical background), and (iii) mechanisms of change in therapy. Several ways of integrating these two therapies are proposed. Schema therapy and narrative psychotherapy are based on contradicting methodologies of structuralism and post-structuralism. Schema therapy develops the concept of schemes, introduced by A. Beck, adding emotions, physiological reactions and memories to its structure, and stresses the importance of using emotion-focused techniques to change them. Narrative psychotherapy is based on theories of dialogical self, introduced by H. Hermans and narrative theories of identity, introduced by T. Sarbin and D. Bruner. Both methods use the idea of multimodal structure of personality. Schema therapy partly uses the idea of distancing from and observing modes, introduced by the third wave of cognitive-behavioral therapies. Narrative psychotherapy uses externalization of symptoms as one of the core techniques. Both methods modify the narrative of the person. Narrative psychotherapy seeks unique events to develop a new narrative of the person according to their values. Schema therapy uses imagery rescripting to meet the needs of a child mode and change emotions experienced in traumatic memory. Both therapies also use internalization of attachment figures. Schema therapy can integrate metaphors from narrative therapy to deal with personality modes. It also can be enriched by treating these modes as sub personalities of narrative psychotherapy and focusing on their narratives and values.
Keywords: narrative psychotherapy; schema therapy